Functional Properties of p-Anisoylated Plasmin-Staphylokinase Complex - Lijnen, H R; Van Hoef, B; Smith, R A G; Collen, D (Thrombosis and Haemostasis, 1993)
The kinetic and fibrinolytic properties of a reversibly acylated stoichiometric complex between human plasmin and recombinant staphylokinase (plasmin-STAR complex) were evaluated. The acylation rate constant of plasmin-STAR by p-amidinophenyl-p’-anisate-HCI was 52 M-1 s-1 and its deacylation rate constant 1.2 × 10-4 s-1 (t½ of 95 min) which are respectively 50-fold and around 3-fold lower than for the plasmin-streptokinase complex. The acylated complex was stable as evidenced by binding to lysine-Sepharose. However, following an initial short lag phase, the acylated plasmin-STAR complex activated plasminogen at a similar rate as the unblocked complex, whereas the acylated plasmin-streptokinase complex did not activate plasminogen. These findings indicate that STAR, unlike streptokinase, dissociates from its acylated complex with plasmin in the presence of excess plasminogen. In agreement with this hypothesis, the time course of the lysis of a 125I-fibrin labeled plasma clot submerged in citrated human plasma, is similar for acylated plasmin-STAR, unblocked plasmin-STAR and free STAR (50% clot lysis in 2 h requires 12 nM of each agent). The plasma clearances of STAR-related antigen following bolus injection in hamsters were 1.0 to 1.5 ml/min for acylated plasmin-STAR, unblocked plasmin-STAR and free STAR, as a result of short initial half-lives of 2.0 to 2.5 min.The dissociation of the anisoylated plasmin-STAR complex and its consequent rapid clearance suggest that it has no apparent advantages as compared to free STAR for clinical thrombolysis.